"A common cause": Sociocultural competence and building and maintaining a fan community. Issue 1 (2nd January 2023) - Harmon, Justin
ABSTRACT: For fans of the band Phish, their primary forum for engaging their fan identity is through participation in the perennial communities that only come into being when the band is on tour. Because of the liminal nature of concerts and tours, the most faithful of fans develop a type of sociocultural competence that helps them acclimate and relate to other members of the music scene to make the most of their finite time together. This sociocultural competence transcends observable aspects of a community and is something that must be learned over time and comes only through immersion in the music community along with a high level of dedication. In short, it is a set of social skills that are only available to the initiated, something that was evidenced by the participants of this study and their commitment to the band, its music, and the scene. Further, while fans come to the music scene to engage their freedom of individuality, many also find that uniqueness is accepted, contributing in a way where the sum is greater than the parts.